PERSEPSI KARYAWAN TERHADAP SISTEM PELAPORAN KECELAKAAN KERJA DAN POTENSI BAHAYA DI PERTAMBANGAN BATUBARA PT. PUTRA KAJANG KALIMANTAN TIMUR - Muhammad Sultan; Emil Riza Putra; Herry Farjam (Poltekkes Kemenkes Padang, 2021)
Work accidents in coal mining still occur frequently, so an accident reporting system is needed as an effort to prevent work accidents. This study aims to explain the perceptions of coal mining employees on the reporting system for work accidents and potential hazards. The research design was descriptive with a sample size of 55 people. Data collection was carried out using a questionnaire. Data were analyzed descriptively. As many as 67.3 % of employees have positive perceptions and 32.7 % of employees have negative perceptions of the work accident reporting system and potential hazards. There are 72.7% of employees consider it important to report accidents and potential hazards. It was found that 30.9 % of employees had experienced work accidents and only 5.4 % of them reported accidents. Employees consider a good accident reporting system, among others, digitally 84.6 % and manually 9.1 %. As many as 90.9 % of employees agree and 81.8 % of employees are willing to report accidents and potential hazards if the company implements a digital-based reporting system. There are still employees who have negative perceptions of the work accident reporting system and potential hazards in coal mining. Therefore, efforts are needed to increase employee perceptions from negative to positive perceptions of the work accident reporting system and potential hazards in coal mining companies.